Księga autografów zwiedzających Zamek. 1928-1929 - Archiwum Biblioteki Kórnickiej (1924-1952) (1928)
Maria Zdzisławowa Czartoryska, Jan Gawroński, Luciana Gawrońska, 15.06.1928, k. 7.
1000,00
Keywords: Księga wpisów